Actions of the hospital infection control commission in confronting the new SARS-CoV-2 corona virus (Research, Society and Development, 2022)
Introduction: With an unknown scenario in the face of the pandemic and the uncertainties on the part of the population and health professionals, doubts have arisen, growing inside and outside health institutions, thus generating a need for systematic and effective action by the control committee of hospital infection (CCIH) in the search for strategies for the reorganization of the units, decision making, elaboration of protocols and training for the health team. Objective: To verify in national and international publications, the main measures and actions implemented by the hospital infection control commission in the face of the new SARS-CoV-2 Coronavirus. Methodology: This is an integrative literature review, produced from the analysis of articles in the Virtual Health Library (VHL), in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Library of Medicine of the United States of America (MEDLINE), Nursing Database (BDENF). Discussion: After carrying out an analytical reading, 08 articles were selected, as they had content that contributed to the development of the study, from the articles found in the databases. With this, it was possible to identify the actions carried out by the hospital infection control commission. Conclusion: The performance of the CCIH is extremely important in the face of the pandemic, and it was challenging for professionals due to the lack of preparation, providing a strategic look so that operational and managerial actions can be organized, prioritized and implemented in a unison.